Aktif tektonik havzalarda AHP-LR modeli kullanılarak sismik tehlike değerlendirmesi: Tokat örneği (Kuzey Anadolu Fay Zonu, Türkiye) - Toprak, Ahmet; Yaşarul, Sevilay (Türk Coğrafya Kurumu, 2026)
The province of Tokat, situated along the North Anatolian Fault Zone (NAFZ), is an active tectonic region that has been subject to destructive earthquakes throughout history. In this study, the seismic hazard potential of Tokat Province has been spatially modelled by integrating the Analytic Hierarchy Process (AHP), based on expert opinion, and data-driven Logistic Regression (LR) methods. The study utilized 11 different parameters, including lithology, fault distance, soil liquefaction, Vs30, slope, and settlement development. To prevent overfitting in the LR model, the number of parameters was statistically reduced to seven key factors. The model was trained using data from areas identified as very high hazard via the AHP. The analysis revealed that the area under the ROC curve (AUC) for the LR model was calculated as 0.952, a value that demonstrates the model’s predictive success. Whilst the AHP model classified 30.5% of the province as very low risk, the LR model expanded the hazardous areas, classifying the Erbaa, Niksar and Tokat basins in particular as High Risk. Surface fractures identified during field observations across the province fully correspond with the LR model’s high-risk predictions. The resulting model provides a reliable basis for regional disaster management and urban planning strategies.
Seismic hazard assessment in active tectonic basins using a AHP-LR model: The case of Tokat (North Anatolian Fault Zone, Türkiye)
Keywords: Sismik Tehlike; Analitik Hiyerarşi Süreci; Lojistik Regresyon; Hibrit Model; Tokat.